The Native Wolbachia Symbionts Limit Transmission of Dengue Virus in Aedes albopictus - Mousson, Laurence; Zouache, Karima; Arias-Goeta, Camilo; Raquin, Vincent; Mavingui, Patrick; Failloux, Anna-Bella (PLoS neglected tropical diseases, 2012)
The chikungunya (CHIK) outbreak that struck La Reunion Island in 2005 was preceded by few human cases of Dengue (DEN), but which surprisingly did not lead to an epidemic as might have been expected in a non-immune population. Both arboviral diseases are transmitted to humans by two main mosquito species, Aedes aegypti and Aedes albopictus. In the absence of the former, Ae. albopictus was the only species responsible for viral transmission on La Reunion Island. This mosquito is naturally super-infected with two Wolbachia strains, wAlbA and wAlbB. While Wolbachia does not affect replication of CHIK virus (CHIKV) in Ae. albopictus, a similar effect was not observed with DEN virus (DENV). To understand the weak vectorial status of Ae. albopictus towards DENV, we used experimental oral infections of mosquitoes from La Reunion Island to characterize the impact of Wolbachia on DENV infection. Viral loads and Wolbachia densities were measured by quantitative PCR in different organs of Ae. albopictus where DENV replication takes place after ingestion. We found that: (i) Wolbachia does not affect viral replication, (ii) Wolbachia restricts viral density in salivary glands, and (iii) Wolbachia limits transmission of DENV, as infectious viral particles were only detected in the saliva of Wolbachia-uninfected Ae. albopictus, 14 days after the infectious blood-meal. We show that Wolbachia does not affect the replication of DENV in Ae. albopictus. However, Wolbachia is able to reduce viral infection of salivary glands and limit transmission, suggesting a role of Wolbachia in naturally restricting the transmission of DENV in Ae. albopictus from La Reunion Island. The extension of this conclusion to other Ae. albopictus populations should be investigated.